The Sophistic Way to Moral Perfection - Pawłowski, Kazimierz (Colloquia Litteraria, 2019)
Morality is a component of culture, variable as much as the whole culture is. It cannot claim absolutization. Natural law is the only constant, ingrained in some way in the moral tissue of a person and revealing itself as its inborn moral sensitivity. Consequently, a morally mature person, with properly developed awareness of innate moral sensitivity, acting in him as a kind of moral instinct, is capable to judge what in this culture is and what is not in keeping with natural law, independently of different state institutions and all other organizations’ promulgations. The individual person is the real creator of culture and he also transmits in some way his characteristic sensitivity to this culture (under the condition that morally sensitive people prevail; as history and modern times teach us this is not always the rule). Therefore, culture and civilization, in a different manner, in accordance with manifold local determinants, makes its own way in its proper rhythm to the state in which absorption of natural law is achieved to its maximum, that is it leads to the state in which the established laws reconstruct natural law as accurately as possible, or at least its spirit. A person as an individual is the subject and creator of culture in all its aspects and that is why he cannot be treated like an object in the context of different cultural values (e.g. ethical, religious and political). If that is the case, culture is degenerated and artificial. Such are the consequences of a sophistic (and mainly Protagoras) science on humans in a specific environment of culture and civilization.